Peran Big Data terhadap Kualitas Data Statistik Indonesia di Era Digital - Yulismah Y (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Increasingly developing technology makes data provision increasingly faster. Providing fast data must also be balanced with maintaining data quality. Every data must follow international standards so that its quality can be recognized. One of these data providers is Big data. Big data can store large and integrated data. Big data can be used anywhere safely and comfortably. The aim of this research is to consider the current importance of Big Data for future statistical data collection. Through a literature review of this research, it was found that Big Data brings benefits by providing data that is fast and accurate and can be found everywhere. This can play an important role in providing data in various sectors so that it can meet the required data sources. Some of the roles that researchers convey in this research are the role of big data in the education sector, the role of big data in the health sector, the role of big data in the business sector, and the role of big dataÂ inÂ government.